Investigations into the Causes and Control of the Growth Arrestment Phenomenon of Sultana. II. Preliminary Experimental Investigations - Saayman, D. (South African Journal of Enology and Viticulture, 2017)
As a continuation of the investigation into the growth abnormalities, called ’growth arrestment phenomenon’ (GAP), which occur extensively in the Sultana vineyards of the Lower Orange River region, field experiments comprising K fertilisation, scheduled irrigation, crop control and specific plant organ and tissue analyses were conducted. Experimental results showed no response to K fertilisation but a promising response to controlled irrigation. Analyses of various organs revealed a faulty carbohydrate metabolism and high N concentrations, probably a result of the fertile soil and high temperatures during the growing season, causing vigorous as well as continued shoot growth after harvest. Specific analyses of affected organs and tissues showed black bunches and shiny spots on leaves to be high in N and Mn and low in K. It is postulated that amongst the major factors causing GAP are the specific climatic and soil conditions which cause poor accumulation of reserves and high N contents. The mechanism by which GAP is caused and practical measures to combat this phenomenon merit urgent further studies.